APOLOGIST OF KOVALIVKA - Baran, Ye. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
The review of book of Nick Lesiuk is the «Linguistic world of modern Galich village (Kovalivka Kolomyia district)». – Ivano-Francovsk: Nova Zorya, 2008. – 328 s.